‘So great a desire’: investigating the BIG MESS construction in Early Modern English - Sommerer, Lotte (Journal of Historical Syntax, 2022)
This paper investigates the BIG MESS construction (e.g. how great a pleasure, too heavy a burden) in Early Modern English (EModE). It presents a diachronic constructional analysis, zooming in on four constructional sub-types, namely [how ADJqualitative a Nsg]Cx, [too ADJqualitative a Nsg]Cx , [so ADJqualitative a Nsg]Cx and [as ADJqualitative a Nsg]Cx. Data from the EEBO corpus are analyzed in order to trace the diachronic development of those templates focusing on their changing frequency and compositionality. Additionally, the paper investigates (changing) lexical biases and the feature of ‘discontinuous modification’ (DM) (e.g. too ADJqualitative a Nsg to-CL, as ADJqualitative a Nsg as-CL, so ADJ a Nsg that-CL). The main theoretical aim is to sketch the constructional network of the BIG MESS family with its various subtypes, discussing the possible form-meaning pairings with their parent and peer relations. Among other things it is shown that the construction had its heydays in Early Modern English and that it is quite productive. As the constructional subtypes differ substantially in their formal and functional features, it will be argued that they are licensed by different constructions with weak or no horizontal connection
Keywords: Usage-based cognitive Construction grammar; Early Modern English; BIG MESS construction; constructional family; parent and peer relations; Diachronic Construction Grammar; non-canonical NPs